Six Didactic Designs for Learning Philosophy through the Development of Skills: The Case of Two Public Secondary Schools in San José, Costa Rica - Cordero Redondo, Joan Javier (2024)
Contemporary research on the teaching of philosophy is extensive; however, in most cases, these studies do not contribute to the knowledge of teaching and proven didactic designs. Therefore, the objective of this research consists of analyzing the limits and possibilities of didactic and methodological designs for teaching philosophy in secondary education, considering the skills education paradigm (Assessment and Teaching of 21st Century Skills, 2010; Griffin et al., 2012), within the framework of the Aprendo en casa strategy of the Ministry of Public Education during the 2020 school year at José Joaquín Vargas Calvo and Sinaí High Schools in San José, Costa Rica. The methodological aspects addressed in this research include an overview of the educational environment of the participants; the professional profile of the teaching staff, and the evaluation of didactic designs and philosophy. To do this, the investigator administered a structured interview to 100 student participants. One of the most timely results of this research is the creation and positive validation of six didactic designs for teaching and learning philosophy in secondary education. Among the conclusions, it is noteworthy that the paradigm upon which the philosophical didactic designs are based seeks to encourage the autonomy of students' thinking, the construction of learning, and the development of skills. This constitutes a suggestive manual of philosophical didactic activities for daily pedagogical work within the skills-based education paradigm. Hence, it is recommended to explore the application of these didactic designs in groups from other grade levels and to investigate new didactic designs in philosophy based on skills-based education.